Експериментальні дослідження турбулентного стану атмосфери за допомогою акустичного вимірювача - Швидкий, О. С. (My University, 2018)
The urgency of studies of the turbulent state of the atmospheric boundary layer is given. The processing of experimental data obtained with the help of an acoustic locator KNURE was performed. The resulting source material was classified according to the principle of matching echoes in the fluctuating layer, in a perturbed layer, completely perturbed by the surface layer. The general characteristic of the data obtained was their difference in the degree of excitation of the air environment. Using the Pearson chi-square consistency criterion the adequacy of the theoretical and experimental data was proved.
Keywords: турбулентність; атмосферна